Pengaruh Manajemen Laba, Struktur Kepemilikan, dan Risiko Sistematis Terhadap Return Saham - Hendrik ES Samosir (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the Effect of Earnings Management, Ownership Structure, and Systematic Risk on Stock Returns. The research method used in this study is a descriptive statistical method. With verification testing using multiple regression (multiple regression). The data used is secondary data, namely the annual reports of companies that are used as samples in the study. The research sample is 12 companies listed on the Indonesia Stock Exchange in 2019-2022 which were taken using the purposive sampling method. The results of this study indicate that Earnings Management, Ownership Structure and Systematic Risk have a positive and significant effect on Stock Returns.